Tax Systems Under Fiscal Adjustment : A Dynamic CGE Analysis of the Brazilian Tax Reform - Lledo, Victor (IMF Working Papers; Working Paper ;, 2005)
This paper uses a dynamic computable general equilibrium model (CGE) to analyze the macroeconomic and redistributive effects of replacing turnover and financial transaction taxes in Brazil by a consumption tax. In order to approximate Brazil's compliance with its fiscal adjustment targets, the proposed reform is subject to a non increasing path for the level of public debt. Despite an increase in the average consumption tax rate in the first years after the reform, a majority of individuals experienced an increase in their lifetime welfare. This result rejects the hypothesis that the on-going fiscal adjustment effort carried on by the Brazilian government was an obstacle to the implementation of a more efficient tax system.